Economic Analysis of Risk through Hazard, Exposure, Sensitivity, and Adaptive Capacity: Implications for Risk Management in Nepal - Adhikari, Rajendra; Paudyal, Kavita (Adhyayan Journal, 2026)
This paper explores the economic impact of climate-sensitive variables like hazard, exposure, sensitivity, and adaptive capacity on risk management in Nepal so as to present evidence-based policy recommendations. It uses an OLS regression model with the secondary data of 77 districts in Nepal in 2022. The findings reveal that the economic risk largely depends on hazard, exposure, and sensitivity as positively influencing factors and the adaptive capacity as having a strong negative impact, which implies the role of the latter in eliminating socio-economic losses. The model is robust as indicated by diagnostic tests, such as the variance inflation factor (VIF) and scale coefficients. The results indicate that effective risk management policies ought to be directed at minimizing the risk levels and sensitivity using early warning systems and resilient infrastructure, and at the same time, enhance adaptive capacity using technical training and allocation of resources. The research proposes that government bodies (federal, provincial, and local) should act in co-ordination with the private sector and other stakeholders to establish resilience over the long run. These climate-sensitive variables will help to address these questions: How can the evidence-based planning and resource allocation be integrated into economic analysis to facilitate sustainable development and increase disaster resilience in Nepal?